Does Femoroacetabular Impingement Syndrome Affect Self-Reported Burden in Football Players With Hip and Groin Pain?. (November 2022) - Scholes, Mark J.; Kemp, Joanne L.; Mentiplay, Benjamin F.; Heerey, Joshua J.; Agricola, Rintje; Semciw, Adam I.; Souza, Richard B.; Link, Thomas M.; Majumdar, Sharmila; King, Matthew G.; Lawrenson, Peter R.; Crossley, Kay M.
Background: It is unknown if football players with femoroacetabular impingement (FAI) syndrome report worse burden than those with other causes of hip/groin pain, and to what extent this is mediated by cartilage defects and labral tears. Hypothesis: Football players with FAI syndrome would report worse burden than other symptomatic players, with the effect partially mediated by cartilage defects and/or labral tears. Study Design: Cross-sectional study. Level of Evidence: Level 4. Methods: Football (soccer and Australian football) players (n = 165; 35 women) with hip/groin pain (≥6 months and positive flexion–adduction–internal rotation test) were recruited. Participants completed 2 patient-reported outcome measures (PROMs; the International Hip Outcome Tool–33 [iHOT-33] and Copenhagen Hip and Groin Outcome Score [HAGOS]) and underwent hip radiographs and magnetic resonance imaging (MRI). FAI syndrome was determined to be present when cam and/or pincer morphology were present. Cartilage defects and labral tears were graded as present or absent using MRI. Linear regression models investigated relationships between FAI syndrome (dichotomous independent variable) and PROM scores (dependent variables). Mediation analyses investigated the effect of cartilage defects and labral tears on these relationships. Results: FAI syndrome was not related to PROM scores (unadjusted b values ranged from −4.693 ( P = 0.23) to 0.337 ( P = 0.93)) and cartilage defects and/or labral tears did not mediate its effect ( P = 0.22-0.97). Conclusion: Football players with FAI syndrome did not report worse burden than those with other causes of hip/groin pain. Cartilage defects and/or labral tears did not explain the effect of FAI syndrome on reported burden. Clinical Relevance: FAI syndrome, cartilage defects, and labral tears were prevalent but unrelated to reported burden in symptomatic football players.